Multiple Classrooms of Life: English, Ideology and 'Sparkle' Moments. Issue 3 (3rd July 2019) - Le Ha, Phan; Dat, Bao
ABSTRACT: This essay comprises multiple sets of dialogues between us as colleagues and friends as we revisit the question of the status of English as a global language. Through the metaphor 'multiple classrooms of life', we share reflections and narratives arising out of our experiences with English that are embedded in our professional work, scholarship, pedagogy and creative interests. Our discussion encompasses a range of artefacts, including excerpts from our diaries, poems, vignettes, visuals, letters, songs and anecdotes. This amalgam of materials represents our personal engagement with English, as distinct from treating the spread of English simply as a metanarrative played out at a remove from personal experience. We reconstruct 'sparkle moments' arising from personal encounters and social interactions that have caused us to reflect on the role of English in our lives. We thus focus on ideology as personally felt and lived from within and through inter-personal interactions.